2009
DOI: 10.4049/jimmunol.0900269
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of CXCR7-Mediated Signaling Events and Inhibition of CXCR4-Mediated Tumor Cell Transendothelial Migration by CXCR7 Ligands

Abstract: CXCR7 binds chemokines CXCL11 (I-TAC) and CXCL12 (SDF-1) but does not act as a classical chemoattractant receptor. Using CCX771, a novel small molecule with high affinity and selectivity for CXCR7, we found that, although CXCR7 is dispensable for “bare filter” in vitro chemotaxis, CXCR7 plays an essential role in the CXCL12/CXCR4-mediated transendothelial migration (TEM) of CXCR4+CXCR7+ human tumor cells. Importantly, although CXCL11 is unable to stimulate directly the migration of these cells, it acts as a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
310
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(332 citation statements)
references
References 31 publications
19
310
3
Order By: Relevance
“…However, we did observe recruitment of β-arrestin to the plasma membrane upon treatment with both ligands in HEK293 cells transiently transfected with CXCR7 and GFP-labeled β-arrestin2 (Fig. 1A), consistent with recent reports of ligand-dependent interactions between these two molecules (15,16). Notably, we did not observe such recruitment in mock transfected HEK293 cells, which express endogenous CXCR4, an alternate receptor for SDF-1α (Fig.…”
Section: Cxcr7supporting
confidence: 78%
See 2 more Smart Citations
“…However, we did observe recruitment of β-arrestin to the plasma membrane upon treatment with both ligands in HEK293 cells transiently transfected with CXCR7 and GFP-labeled β-arrestin2 (Fig. 1A), consistent with recent reports of ligand-dependent interactions between these two molecules (15,16). Notably, we did not observe such recruitment in mock transfected HEK293 cells, which express endogenous CXCR4, an alternate receptor for SDF-1α (Fig.…”
Section: Cxcr7supporting
confidence: 78%
“…It has also been proposed that CXCR7 acts as a coreceptor for CXCR4 (11,13), as the two receptors form heterodimers in the context of overexpression in transiently transfected cells. It has also been proposed that ligand binding to CXCR7 may result in crosstalk with CXCR4 mediated by intracellular signaling molecules (15). More recently, it has been demonstrated that CXCR7 interacts with β-arrestin in a liganddependent manner (15)(16)(17), resulting in ligand internalization, but without any assessment of changes in signaling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,45 Recent studies found an association between CXCR7 and the adaptor protein b-arrestin2. [47][48][49] Interactions of arrestins with different receptors have been shown to facilitate activation of the MAPK cascade, a signaling pathway, which is known to regulate also MMPs. 50 High production of MMPs by RASFs has been identified as a major mechanism of joint destruction in RA.…”
Section: Dna Methylation Regulates the Expression Of Cxcl12 E Karouzamentioning
confidence: 99%
“…CXCR7 is unlikely to be mediating the invasion response to CXCL12, since AMD3100 does not inhibit CXCR7 signaling as measured by ␤-arrestin recruitment. 44 The mechanism by which CXCR4 transactivates EGFR for invasion in vivo is likely to be due to EGFR ligand release, since the ADAM17 inhibitor TAPI-2 blocked CXCL12-induced invasion. However, EGF-induced invasion was not inhibited by TAPI-2 at 0.5 mol/L, indicating that EGFinduced invasion does not involve relay of EGFR ligand signaling.…”
Section: In Vivo Invasion Of Hnscc 2863mentioning
confidence: 99%